MEDIA PENDATAAN SATWA LIAR BERBASIS WEB DAN MOBILE - Putra, Farozi Rizky; Sancoko, Sulistyo Dwi (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Indonesia, with its high biodiversity, faces significant challenges in conserving wildlife threatened by climate change, habitat destruction and illegal trade. This research aims to develop a web and mobile-based